2018
DOI: 10.1177/0047287518775781
|View full text |Cite
|
Sign up to set email alerts
|

Is the Airline Trustworthy? The Impact of Source Credibility on Voluntary Carbon Offsetting

Abstract: Airlines have introduced voluntary carbon offsetting (VCO) products to encourage consumers to mitigate emissions from their air travel. However, literature has suggested a low VCO adoption partly because of low perceived credibility. This study investigates the impact of source credibility (expertise and trustworthiness) on air travelers’ purchase intention for aviation VCO products. This is the first study to conceptualize and test the influence of source credibility on air travelers’ carbon offsetting behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 75 publications
0
47
0
Order By: Relevance
“…Thus, the celebrity in the advertisement would enhance brand awareness and attract their followers and convince them to try the products (Chan, Leung Ng, & Luk, 2013). Credible celebrities were also found effective to convince the consumer to purchase environment-friendly products (Eren-Erdogmus et al, 2016; Khandelwal & Bajpai, 2011; Zhang et al, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Thus, the celebrity in the advertisement would enhance brand awareness and attract their followers and convince them to try the products (Chan, Leung Ng, & Luk, 2013). Credible celebrities were also found effective to convince the consumer to purchase environment-friendly products (Eren-Erdogmus et al, 2016; Khandelwal & Bajpai, 2011; Zhang et al, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Soesilo, Gunadi, and Arimbi [46] found that consumers' perceived risk was lower when the product was produced by a credible company but endorsed by a less credible source, than when it was produced by a less credible company but endorsed by a more credible source. Zhang et al [47] investigated the impact of source credibility (expertise and trustworthiness) on air travelers' purchase intentions in relation to aviation voluntary carbon offsetting products. The result showed that trustworthiness has a significant positive impact on purchase intentions, while the impact of expertise is not significant.…”
Section: Corporate Credibilitymentioning
confidence: 99%
“…In this sense, tourists are in a situation where they must decide on various aspects that influence their overall emissions. For example, if they avoid long-haul flights; choose sustainable modes of transport over unsustainable ones; avoid activities that use a lot of energy, such as buying imported food [10,11]; or purchase carbon offsets [12], then they can keep their environmental footprint low. However, their decisions are rooted in their attitudes towards the environment.…”
Section: Introductionmentioning
confidence: 99%